A Review of the Health Impact of Nicotine Pouches - Chmiel, Radosław; Michałka, Daria; Papachristoforou, Natalie; Gałuszka, Zuzanna; Makar, Monika; Bartuś, Tomasz; Tekiela, Natalia; Bąk, Emilia; Głowacka, Justyna; Kocjan, Aleksandra (Quality in Sport, 2025)
Introduction and Purpose of Research Nicotine pouches, popular especially among young people, are smokeless alternatives to traditional tobacco. Placed in the mouth, they release nicotine absorbed through the mucosa, reducing withdrawal symptoms and avoiding harmful tobacco smoke. Often used for smoking cessation, they are considered lower-risk than smoking and may help reduce smoking rates. The aim of this review is to summarize the current knowledge on the impact of nicotine pouches on overall human health. Review Methods The review is based on 39 articles found in PubMed databases published between 2006–2024. Conclusion While nicotine pouches and snus are marketed as lower-risk alternatives to smoking, their health implications are still significant. These products, popular among young adults and athletes, may help with smoking cessation but carry risks, particularly with long-term use. Research suggests nicotine pouches and snus may have no performance-enhancing effects in sports and could impair physical performance, including endurance and strength. Moreover, their use is linked to various health concerns such as cardiovascular issues, type 2 diabetes, oral mucosal changes, and decreased sperm count. Snus has been associated with a modest increase in cardiovascular disease risk, although the risks are lower than smoking. Additionally, smokeless tobacco use is linked to an increased risk of oral squamous cell carcinoma, especially in women. The use of snus during pregnancy has also been linked to higher risks of post-neonatal mortality and other adverse outcomes. Despite these findings, there is a need for more extensive, well-controlled studies to fully understand the long-term health effects of smokeless tobacco products and their role in public health.